HOW TO DESIGN GENETICALLY MODIFIED FOOD LABELING REGULATION IN INDONESIA - TAKING SCIENCE, TRADE LAW, AND INDONESIAN DEMANDS SERIOUSLY - Wahidin, Dasep; Purnhagen, Kai Peter (Indonesia Law Review, 2020)
The paper critically evaluates the current Indonesian genetically modified (GM) food labeling regime as it is embedded in the international trade law and policy system. This research proposes a GM food labeling regulation for Indonesia based on the socio-economic demands of Indonesia on the one hand and the demands of international trade law and policy on the other. It answers the following research questions: What are the legislative requirements for labelling of genetically modified organisms (GMOs) according to Indonesian law? How should Indonesian law on GM food labelling be designed to meet the interests of its peoples and provide access to foreign markets? We highlight the major weaknesses of the Indonesian GM food labelling law from the perspective chosen in this paper, such as the dependence on regulation from bigger trading blocs, lack of consideration for the socio-economic characteristics of Indonesia, and a low level of compliance. To overcome these shortcomingss, we propose a novel GM food labeling regulation for Indonesia that is based on the concept of Food Safety Objective/Appropriate Level of Protection (FSO/ALOP) applicable to developing countries.